Hydrodynamic Condition of Tides and Wave Diffraction in the Estuary of Jeneberang River - Karamma, Riswal; Pallu, Muhammad Saleh; Thaha, Muh Arsyad; Hatta, Mukhsan Putra (INTEK: Jurnal Penelitian, 2020)
The coastal hydrodynamic pattern around the estuary is determined by the wave, river discharge, and the tidal condition which work simultaneously. The wave factor contributes to more dominant influence on estuaries located in the open sea. Wave coming towards the coast can generate current on the coast. The current pattern around the estuary is determined mainly by the magnitude of the angle formed between the incoming wave and the coastline. The objective of this research is to analyze the wave diffraction patterns and the length of tidal propagation towards the direction of the coast in the estuary. Investigated area is situated in the estuary of Jeneberang River. The analysis of tidal propagation and wave diffraction covers a reach of 4270 meters upstream. Data collected include bathymetric, wind, and tidal data. Furthermore, the result of this analysis can be used as an input in efforts to manage and develop the coastal area in the estuary of Jeneberang River. The length of the tidal propagation in the estuary of Jeneberang River is approximately 1220 meters upstream. Wave diffraction occurs from the north, northwest, and west direction. The highest wave diffraction came from the west direction with the value of 0.73 m and the lowest wave diffraction came from the north direction with the value of 0.04 m.